„Mistrz musi potwierdzić ucznia, uczeń potwierdza mistrza w jego roli i pozycji”. O relacjach Karola Szymanowskiego i Zygmunta Mycielskiego - Mielcarek-Krzyżanowska, Barbara (Res Facta Nova, 2021)
The special relationship that developed during the second half of the 1920s between Karol Szymanowski and Zygmunt Mycielski, composers from two different generations, lasted until Szymanowski’s death in 1937. In this relationship there was a combination of experience, wisdom and knowledge, identified with the position of the master, and supported by his having overcome the reluctance to share them with a young novice in composition, just entering the field of music. The attitude of the pupil often lacked the usual boundless trust in themaster, compensated for by Mycielski through enormous respect and fascination with Szymanowski’s stance. The two composers were linked by background, respect for tradition, and by dramatic events which at different moments in history deprived them of contact with the material heritage of their ancestors. The bond they built between them turned not only into deep friendship but also a special kind of spiritual closeness. They affirmed each other in their roles, giving this bond an almost symbolic dimension.